2020
DOI: 10.1007/s00415-020-10145-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Acute necrotizing myelitis and acute motor axonal neuropathy in a COVID-19 patient

Abstract: A 61-year-old woman with COVID 19 infection developed acute necrotizing myelitis (ANM) and acute motor axonal neuropathy (AMAN), a rare variant of Guillain-Barré syndrome (GBS) without systemic signs of infection. MRI of the cervical spine demonstrated longitudinally extensive transverse myelitis, and EMG was consistent with the diagnosis of AMAN. CSF testing was negative for SARS-CoV-2. High dose steroids followed by plasma exchange were administered, and the patient made a clinical recovery. Immunotherapy ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
95
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(108 citation statements)
references
References 5 publications
1
95
0
12
Order By: Relevance
“…We reviewed all the cases excluded by Abu-Rumeileh et al also and found no positive ganglioside antibodies among those excluded patients. We have identified seven more reported individual cases, which have not been included in any case review to date [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Including our current case, there are 83 individual cases of COVID-19 related GBS or MFS being reported to date.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…We reviewed all the cases excluded by Abu-Rumeileh et al also and found no positive ganglioside antibodies among those excluded patients. We have identified seven more reported individual cases, which have not been included in any case review to date [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Including our current case, there are 83 individual cases of COVID-19 related GBS or MFS being reported to date.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…Complete recovery was seen in 1/18(5.6%) ( Chow et al, 2020 ), moderate improvement in 5/18 (27.7%) ( Zhou et al, 2019 ; Novi et al, 2020 ; Munz et al, 2020 ; Sarma et al, 2020 ; AlKetbi et al, 2020 ), mild improvement in 9/18(50.0%) ( Zoghi et al, 2020 ; Maideniuc et al, 2020 ; Valiuddin et al, 2020 ; Masuccio et al, 2020 ; Zachariadis et al, 2020 ; Águila-Gordo et al, 2020 ; Sotoca et al, 2020 ; Baghbanian et al, 2020 ), no improvement in 1/18(5.6%) ( Kaur et al, 2020 ) and 2 deaths (11.1%) ( Chakraborty et al, 2020 ; Abdelhady et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Myelitis was associated with encephalitis in 2 cases ( Zoghi et al, 2020 ; Novi et al, 2020 ), with optic neuritis in 1 case ( Novi et al, 2020 ), and with GBS in 3 cases (all of them with axonal-loss predominant polyneuropathy) ( Maideniuc et al, 2020 ; Valiuddin et al, 2020 ; Masuccio et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a 61-year-old female with COVID-19, spinal MRI revealed longitudinally extensive transverse myelitis [9]. The patient profited from repeated rounds of plasma exchange [9]. In addition to several other cases with SARS-CoV-2-associated myelitis in adults [10,11], SARS-CoV-2associated myelitis has been also reported in children [12].…”
mentioning
confidence: 88%
“…Though myelitis has been reported in only single patients, it should not be missed, as delayed treatment may have strong implications on the outcome. In a 61-year-old female with COVID-19, spinal MRI revealed longitudinally extensive transverse myelitis [9]. The patient profited from repeated rounds of plasma exchange [9].…”
mentioning
confidence: 99%